Pengaruh Partisipasi Anggaran terhadap Kinerja Manajerial dengan Self Efficacy, Desentralisasi dan Budaya Organisasi sebagai Variabel Pemoderasi pada Perbankan - Exsha Tri Tut Wuri Handayani; Zainal Ilmi; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Exsha Tri Tut Wuri Handayani. Effect of Managerial Performance Against Budget Participation With Self Efficacy, Decentralization and Cultural Organization as moderating variables on Banking. This study aimed to examine the effect of participation Budget effect on managerial performance BNI Samarinda, to test whether self-efficacy were able to moderate the relationship between budgetary participation and managerial performance at BNI Samarinda, to test whether Decentralization able to moderate the relationship between budgetary participation and managerial performance BNI Samarinda, and to test whether organizational culture is able to moderate the relationship between budgetary participation and managerial performance at BNI Samarinda. Results with Partial assay demonstrated by the partial test result that the variable Participation budget affect the performance managerial BNI Samarinda, the variable Self Efficacy able to moderate the relationship between budgetary participation and managerial performance at BNI Samarinda, variable Decentralization able to moderate the relationship between budgetary participation and performance Samarinda BNI managerial and organizational culture variables able to moderate the relationship between budgetary participation and managerial performance at BNI Samarinda.Keywords: Participation budget, self-efficacy, decentralization and organizational culture as well as the moderating variable managerial performance.